Consumerism with Tawhidic paradigm activism with the community in the neighbouring masajid - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (2020)
This study postulates that consumerism activism can be sustained with Tawhidic paradigm through the involvement of local community with masajid. A few masajid have been selected based on the neighbouring to IIUM within 10KM radius. Consumerism activism is part of the SDG No 12 on responsible consumption and production. This study focuses on responsible consumption component, particularly on the awareness part. The study uses focused group and participant observation to obtain views of the participants in the DEBA KENMS SDG Flagship 2019 project. The results of the study suggest that there is very little awareness on consumerism as a whole and almost none on the Tawhidic consumerism awareness despite frequenting to masajid to perform prayers and to listen to sermons and lectures. The study proposes for more activities and concerted efforts between IIUM and the neighbouring community entities.